Influence of exposure to nicotine during pregnancy on the learning and memory for adult offspring - Ma, Xing-Dui (Exp Ther Med, 2018)
We aimed to investigate the indirect influence of exposure to nicotine during pregnancy on the learning and memory of adult offspring mice. Thirty pregnant C57 mice were randomly divided into either the control group (CON) or the nicotine group (NIC), with 15 mice each. The CON group was given access to drug-free water, and the NIC group was given 60 g/ml nicotine in drinking water. Sixteen adult mice were randomly selected from the 8 litters for Morris water maze test. The level of products of related factors in the hippocampus of mice in the NIC and the CON groups were compared using the (1)H-MRS method. The escape latency time that the adult offspring mice in the NIC group took in the place navigation test was significantly longer than that of the CON group. In addition, the NIC group took longer time to arrive at the plate than the CON group (P<0.05). mRNA and protein levels of NR1 in the hippocampus of the NIC group was significantly higher than that in the CON group (P<0.05).α7nACh mRNA in the hippocampus of the NIC group was not significantly different from that of the CON group (P>0.05), while the expression levels of α7nACh protein in the hippocampus of the NIC group was significantly lower than that in the CON group (P<0.05). Detection of protein level of muscarinic receptors in the hippocampus of adult offspring mice in the NIC group showed that when compared to the CON group, the expression levels of M1, M3, M5 of the NIC group was not significantly different from that of the CON group (P>0.05). Therefore, exposure to nicotine during pregnancy can cause damage to the learning ability of adult offspring mice but do not significantly influence their working memory.